Chronic pelvic pain syndrome in women: clinical covariates and comorbidity patterns - Weinschenk, Stefan; Topbas Selcuki, Nura Fitnat; Strowitzki, Thomas; Gerhardt, Axel; Zivanovic, Oliver; Feißt, Manuel (Pain and therapy, 2025)
Introduction: Chronic pelvic pain syndrome (CPPS) in women is a debilitating condition with a high prevalence (5–25%), yet its etiology remains unclear. This prospective observational study aimed to identify clinical and medical history covariates associated with CPPS to elucidate potential pathophysiological mechanisms. Methods: A total of 225 women were evaluated in a gynecological pain clinic in Germany, including 41 patients with CPPS (≥ 6 months of lower abdominal pain) and 184 control patients undergoing routine gynecological screening. Exclusion criteria included pregnancy, pelvic malignancy, acute pelvic inflammation, and abnormal uterine bleeding. Covariates were assessed through structured clinical history and physical examination. Results: Significant associations with CPPS were observed for prior pelvic surgery (72% vs. 45%, p = 0.003), bowel constipation (37% vs. 11%, p = 0.002), history of endometriosis (33% vs. 10%, p = 0.043), and prior trauma (27% vs. 11%, p = 0.013). In contrast, there were no significant differences in rates of depression (p = 0.376), use of psychopharmaceuticals (p = 0.757), pelvic floor abnormalities (p = 0.503), uterine retroversion (p = 0.330), or pelvic congestion (p = 0.455). Dysmenorrhea (59% vs. 42%) and vulvar pain (31% vs. 8%) were more frequent in the CPPS group, though not statistically significant. No differences were found in delivery mode, use of intrauterine devices, analgesics, hormonal replacement therapy, and other medications, or comorbidities such as diabetes, thyroid disease, hypertension, other pain diseases, or musculoskeletal disorders. Conclusions: CPPS was not associated with several commonly suspected cofactors, including psychosomatic factors, pelvic congestion, or pelvic floor dysfunction. The findings suggest the existence of two subgroups of CPPS, the endometriosis-associated type and the neurovegetative type, associated with prior pelvic surgery, constipation, and trauma. This concept allows for the development of new targeted therapeutic strategies to successfully treat CPPS.